Pengaruh Ekstrak Daun Karamunting (Rhodomyrtus tomentosa (Aiton) Hassk.) Untuk Mengendalikan Spodoptera frugiperda J. E. Smith - Hidayah, Lyly; Rosa, Helda Orbani; Pramudi, Muhammad Indar (www.ulm.ac.id, 2025)
Spodoptera frugiperda J. E. Smith (Fall Armyworm) is a pest that attacks corn and other economically important crops. S. frugiperda larvae can damage all parts of the corn plant including stems, leaves, shoots, tillers, and even the leaves of young plants can be damaged. This research aims to determine the effect of R. tomentosa leaf extract in controlling S. frugiperda. The method used was research using a Completely Randomized Design (CRD) with 6 treatments and 2 replications, resulting in 24 experimental units. The treatment involved R. tomentosa leaf extract at different doses and application methods by dipping the larvae and spraying the leaves. As a result, the life cycle of S. frugiperda lasts 32-54 days and extract doses of 10 ml (95%) and 8 ml (85%) are effective in killing larvae, while lower doses also have a significant effect.